Study on the Law and Control Mechanism of Slope Sliding Instability Under Hanging Wall Coal Mining - Junpeng Li; Wencai Wang; Hongbo Yao; Jingjing Yan; Zhenyu Pei (Advances in Civil Engineering)
The clarification of the relationship between overburden movement, slope deformation damage, instability, sliding, and control is essential for the safe and efficient recovery of resources when using the room and pillar mining method for recovering trapped coal in edge areas. This study focuses on the engineering background of the Zhongmei Pingshuo Anjialing Open pit Mine and employs a combination of theoretical analysis, laboratory experiments, and industrial applications to investigate the overburden movement as a driver of slope instability and sliding, and its control. First, a physical and numerical slope model was established to reveal the evolution patterns, formation mechanisms, and relationships of the slope’s “three horizontal zones” with slope instability and sliding. It was found that composite mining in the underlying coal seam tends to create a “circular sliding surface,” shear sliding zone, and localized instability of the slope. Second, a “masonry beam” mechanical model was established to reveal the relationship between overburden movement during edge coal extraction and the two sliding patterns of key rock mass B with slope stability, indicating that the main causes of slope instability and sliding are the repetitive movement of the “masonry beam,” the continual forward migration of the “three horizontal zones,” and the horizontal thrust generated by the rotation of key rock mass B. Finally, a backfill foot control technology aimed at controlling the rotation of the key rock mass B was proposed and analyzed through simulations. This technology was found to not only effectively change the fracture degree of the hinged rock mass but also to suppress the rotation of key rock mass B and the migration direction of the 1360 platform, achieving effective control over slope instability. Based on these findings, engineering applications and validations were conducted, forming a slope stability control system under edge coal extraction.